Rituximab Treatment of Adult Patients with Steroid-Resistant Focal Segmental Glomerulosclerosis - Fernandez-Fresnedo, Gema (American Society of Nephrology, 2009)
Background and objectives: Isolated case reports have shown a beneficial effect of rituximab on pediatric patients with primary FSGS, but there is no information about rituximab treatment of FSGS in adults. Design, setting, participants, & measurements: All patients who had biopsy-proven FSGS and were treated with rituximab in Spain were identified, independent of their positive or negative response, among the nephrology departments that belong to the Spanish Group for the Study of Glomerular Diseases (GLOSEN). Their characteristics and outcome after rituximab treatment were studied. Results: Eight patients were identified. Rituximab failed to improve nephrotic syndrome in five of eight patients, who continued to show massive proteinuria and exhibited a rapidly deteriorating renal function in two cases. Among the remaining three patients, two of them showed an improvement of renal function and a remarkable proteinuria reduction and one experienced a beneficial but transitory effect after rituximab. There were no differences in clinical or laboratory characteristics or in the CD20 B lymphocyte count after rituximab between these three patients and the five who had a negative response. The only difference was in the regimen of rituximab administration: Whereas the five patients with a negative response received only four weekly consecutive infusions of 375 mg/m(2), the three remaining patients received additional doses of rituximab. Conclusions: Only a minority (three of eight) of patients in our series of adult patients with FSGS showed a positive influence of rituximab. More studies are necessary to characterize further the optimal dosages and the mechanisms of action of rituximab in FSGS.